2021
DOI: 10.1186/s12890-021-01785-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study in severe eosinophilic asthma patients refractory to anti-IL5 biological agents treated with benralizumab in Spain (ORBE study)

Abstract: Background Benralizumab, a monoclonal antibody targeting the human interleukin-5 (IL-5) receptor (IL-5R), was used before marketing authorisation in Spain in a real world setting as part of an early-access programme (EAP) to treat patients with severe eosinophilic asthma with prior insufficient response or intolerance to anti-IL5 treatment (mepolizumab or reslizumab). The objective of this study is to describe the patient profile candidate for treatment and to assess benralizumab effectiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In our series, functional parameters improved after treatment with benralizumab in both groups (to a greater extent in those previously treated with omalizumab, +302mL, but also in those treated with mepolizumab, +144mL), although the differences were not statistically significant, probably due to the small sample size. Other real-life studies on the efficacy of benralizumab after switching from anti-IL5 biological treatment 28 , 29 or omalizumab obtain efficacy data similar to those found in our series. 26 …”
Section: Discussionsupporting
confidence: 87%
“…In our series, functional parameters improved after treatment with benralizumab in both groups (to a greater extent in those previously treated with omalizumab, +302mL, but also in those treated with mepolizumab, +144mL), although the differences were not statistically significant, probably due to the small sample size. Other real-life studies on the efficacy of benralizumab after switching from anti-IL5 biological treatment 28 , 29 or omalizumab obtain efficacy data similar to those found in our series. 26 …”
Section: Discussionsupporting
confidence: 87%
“…In this regard, we have seen that some RWE studies are beginning to provide interesting evidence. [99][100][101][102][103][104][105][106][107][108] In the context of national and international registries and large databases, RWE studies can go beyond one of their most significant limitations, which is the low number of patients examined. 117,118 Big data obtained from networks and registers will also allow us to define alternative treatment schemes and dosages, but it is currently necessary to refer to those available.…”
Section: Complementary Results Between Clinical Trials and Real-life ...mentioning
confidence: 99%
“…Other very recent observational studies, retrospective studies, and multicentre studies confirmed that patients with SEA and heterogeneous baseline characteristics treated with benralizumab showed clinically significant improvement in asthma control, QoL, and OCS-sparing effect. 106 , 107 To identify new biomarkers with potentially predictive characteristics, a group of Italian researchers conducted real-life studies on anti-IL-5/anti-IL-5R mAbs using a proteomic approach. They found interesting and innovative data, such as increased oxidation levels of ceruloplasmin and transthyretin in patients treated with benralizumab and apolipoprotein A1 oxidation after mepolizumab treatment ( Table 4 ).…”
Section: Real-life Studies: Translating Evidence Of Clinical Trials I...mentioning
confidence: 99%
“…Other studies have also explored the effect of switching to another mAb on residual disease after blocking the IL-5 pathway. The ORBE study, an observational, retrospective, multicentre study in real-life conditions in Spain, characterized the patient profile and evaluated the effectiveness of at least the first three benralizumab doses in 19 severe eosinophilic asthma patients, refractory to anti-IL5 mAbs [78]: 88.9% of the included patients had been previously treated with mepolizumab, and 11.1% with reslizumab, although in some cases, there was a washout period between previous treatment and benralizumab treatment initiation at the investigator's discretion. The J Investig Allergol Clin Immunol 2023; Vol.…”
Section: How To Proceed In the Event Of Suboptimal Response Switching...mentioning
confidence: 99%